Creating a Fellowship Curriculum in Patient Safety and Quality. (January 2016) - Abookire, Susan A.; Gandhi, Tejal K.; Kachalia, Allen; Sands, Kenneth; Mort, Elizabeth; Bommarito, Grace; Gagne, Jane; Sato, Luke; Weingart, Saul N.
The authors sought to create a curriculum suitable for a newly created clinical fellowship curriculum across Harvard Medical School–affiliated teaching hospitals as part of a newly created 2-year quality and safety fellowship program described in the companion article "Design and Implementation of the Harvard Fellowship in Patient Safety and Quality." The aim of the curriculum development process was to define, coordinate, design, and implement a set of essential skills for future physician-scholars of any specialty to lead operational quality and patient safety efforts. The process of curriculum development and the ultimate content are described in this article.